Observations in Natural History : With an Introduction on Habits of Observing, as Connected with the Study of that Science - Jenyns, Leonard (Place of publication not identified : publisher not identified, 1846)
Although devoted to his parish, Leonard Jenyns (1800-93) combined his clerical duties with keen research into natural history. Notably, he was offered the place on the Beagle that later went to Charles Darwin. His numerous works include A Manual of British Vertebrate Animals (1835) and Observations in Meteorology (1858), both of which are reissued in this series. First published in 1846, the present work was originally intended as a companion volume to Gilbert White's acclaimed Natural History and Antiquities of Selborne (1789), which Jenyns had copied out as a student at Eton. The product of two decades of meticulous observation of Jenyns' surroundings in eastern England, the text includes journal entries with careful records on a wide variety of wildlife, including quadrupeds, birds, reptiles, fish, insects and molluscs. Also featuring a detailed calendar of periodic phenomena, this work illuminates the rhythms and quirks of the natural world in England.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).